(untitled) (Світ фінансів, 2017)
Артус М. М. Державне регулювання ціноутворення в умовах ринкових відносин. Розглянуто необхідність державного регулюючого впливу на ринкове ціноутворення та запропоновано напрямки використання державою системи цін як інструменту забезпечення соціально-економічного розвитку суспільства. Artus M. Government control of pricing in the conditions of market relations. The necessity of state regulative influence is considered on the prices forming and directions of the state use of the system of prices are offered as the instrument of providing of socio-economic development of society.